1995
DOI: 10.1073/pnas.92.8.3406
|View full text |Cite
|
Sign up to set email alerts
|

Decrements in auditory responses to a repeated conspecific song are long-lasting and require two periods of protein synthesis in the songbird forebrain.

Abstract: Earlier work showed that playbacks of con- Songbirds use their songs and calls to communicate with members of their own species. Male songbirds typically learn these vocalizations from adult conspecifics during a sensitive period in development. These learned songs and calls can differ markedly between individuals, though they also share species-typical features (1-3). Much is known about the brain pathways birds use for the production of learned vocalizations (4, 5), but our understanding of circuits that dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
315
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(336 citation statements)
references
References 22 publications
(28 reference statements)
20
315
1
Order By: Relevance
“…Measurement of long-term response habituation in NCM, by both electrophysiology and the study of the song stimulation-induced up-regulation of ZENK, has suggested that this area might encode the long-lasting sensory memory of the TUT (31,40). Other experiments point to the fact that NCM and CM might be involved in short-term plasticity related to song discrimination (18,19,48). The greater representation of TUT and BOS revealed by fMRI in our experiments therefore might reflect an important aspect of the sensory memory for these developmentally salient familiar stimuli.…”
Section: Familiar Song Stimuli Show Selective Differential Topographymentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of long-term response habituation in NCM, by both electrophysiology and the study of the song stimulation-induced up-regulation of ZENK, has suggested that this area might encode the long-lasting sensory memory of the TUT (31,40). Other experiments point to the fact that NCM and CM might be involved in short-term plasticity related to song discrimination (18,19,48). The greater representation of TUT and BOS revealed by fMRI in our experiments therefore might reflect an important aspect of the sensory memory for these developmentally salient familiar stimuli.…”
Section: Familiar Song Stimuli Show Selective Differential Topographymentioning
confidence: 99%
“…In parallel with song motor learning, auditory song selectivity gradually emerges during development (13)(14)(15)(16)(17). Robust sensory responses to auditory stimuli have been recorded in the primary auditory area in the caudal telencephalic region (field L), the caudomedial nidopallium (NCM), the caudal mesopallium (CM), and the caudomedial ventral hyperstriatum (18)(19)(20)(21), as well as in the song nuclei HVC, LMAN, X, and nucleus interface of the nidopallium (22)(23)(24)(25)(26)(27)(28). Sensory representation of birdsong in the song nuclei and the secondary auditory areas NCM and CM is characterized by response selectivity to song ownership, familiarity, and species-specific features.…”
mentioning
confidence: 99%
“…Dorsocaudal NCM neurons are known to habituate to repeated presentation of song stimuli, but we did not observe substantial habituation in our recordings in ventral NCM (as in ref. 40; see also SI Results). Three recording/playback periods consisted of a baseline aCSF retrodialysis (30 min), followed by 30 min of either estradiol (30 μg/mL) or FAD (100 μM) retrodialysis, and then followed by 30 min of washout with aCSF.…”
Section: Methodsmentioning
confidence: 99%
“…We chose auditory regions, because a few subunits/subtypes appeared to have some differential expression relative to the surrounding subdivision (mGluR1 in caudal N for example; Fig. 2), and these regions are involved in auditory processing of learned vocalizations (Chew et al, 1995; . Expression profiles of 21 glutamate receptor subunits/ subtypes from the four glutamate receptor subfamilies in adult zebra finch male brain.…”
Section: Unique Differential Expression In Vocal Brain Areasmentioning
confidence: 99%